Pengembangan GIS untuk Pemetaan Covid-19 dengan Implementasi Location Based Service dan Open Source Map - Nur Fazheera Algadri; Arnita Irianti; Dian Megah Sari (Indonesian Society of Applied Science, 2021)
The spread of Covid-19 is very fast, various efforts are being made to prevent the spread of Covid-19 and provide information about it. Especially in the area of ​​West Sulawesi Province, information about the development of Covid-19 can be accessed through a website that has been provided by the government, namely Covid Sulbar. There is a development of a Geographic information system for Covid-19 mapping with the implementation of Location based services and open source maps. This study aimed to build and implement a system as a solution to the problems currently being faced by the community related to the Covid-19 pandemic and the new normal era. The method used was literature study, observation, and interviews. The device development model used in this research was the Waterfall development model. The results showed that the results of the system development which had been carried out could be drawn from several conclusions that this research produces a Geographic Information System (GIS) regarding the distribution map and status of the Covid-19 zone. Geographical Information Systems (GIS) are easily accessible by users simply by using a web browser. With the GIS-COV website, it could help the public to see and find out information on the condition of an area related to the number of cases and the status of the level of the spread of Covid-19. With the GIS-COV website, the public could find out the number of spread of Covid-19 and certain zones with the highest and lowest levels of spread.